Analisis Model Rantai Markov Waktu Kontinu pada Model Transmisi dan Vaksinasi COVID-19: Studi Kasus Provinsi DKI Jakarta - Rifaldy Atlant Tungga (Jurnal Simki Postgraduate, 2024)
In 2019, the Novel Coronavirus was discovered in Wuhan, China, and later named the disease caused by the virus, called COVID-19. On March 31, 2020, the Indonesian government announced that COVID-19 was a pandemic. Previously, many mathematical models have been used to capture the transmission of this disease. In this paper, a new mathematical model is introduced, namely the continuous-time Markov chain modeling of SIRV, which takes into account the probabilities between events of several groups of individuals, namely the susceptible (S), infected (I), recovered (R), and vaccinated (V) groups. Thus, it is considered to provide more realistic results compared to deterministic models. Using a period of approximately one year, it was obtained that vaccination carried out with a vaccination rate ν=0.002 was considered ineffective.